Analisis Faktor-Faktor yang Berhubungan dengan Keberhasilan Organisasi Pembelajar - , Mahbubah Srimulatsih ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objectives on this research are to analyze the relationship between organization culture, senior management commitments, manager skill, employee attitude, organization of work, and human resources as a successful learning organization at PT. Bank Riau Kepri. The research population was 276 employeesat the main office of Bank Riau KepriPekanbaru and the research samples were 73 employees at the main office of Bank Riau KepriPekanbaru from all level and division.A quota sampling was conducted to 73 employees. The primary data collection was conducted by distributing questionnaires and respondentsâ responses measured using Likert Scale.Descriptive statistics analysis and inferential statistical analysis (partial correlation and multiple linear regression) were used to analyze data in this research. This researchâs result shows that there is a positive relationship betweenorganization culture, senior management commitments, manager skill, employee attitude, organization of.work, and human resources as a successful learning organization.